Detection of plant viruses in mosses and higher plants Deschampsia аntarctica in the region of Argentina Islands in Antarctica - I. G. Budzanivska; T. P. Shevchenko; E. S. Shytikov; S. V. Olijnyk; V. P. Polishchuk (Ukrainian Antarctic Journal, 2005)
Due to the importance of plant virus research in Antarctica, the aim of this work was to investigate the diversity and spreading of phytoviruses among higher and elementary plants which are endemic to the region of Argentina islands. Deploying indirect and sandwich ELISA, we analyzed plant samples from  Academician Vernadskiy and the biggest islands of archipelago including Petermann, Jaolur, Skua, Wienke, Winter, Barthelot, and cape Rassmunsen, for the presence of phytoviruses’ antigens. Among the viruses tested were Tobacco mosaic virus, Cucumber green mottle mosaic virus, Potato virus X, Cucumber mosaic virus, Alfalfa mosaic virus, and Tomato spotted wilt virus. Our study revealed antigens of viruses belonging to various taxonomic groups in Deschampsia аntarctica plants and mosses from Barbilophozia and Polytrichum genera. Tobacco mosaic virus and Cucumber green mottle mosaic virus (Tobamovirus), Cucumber mosaic virus (Bromoviridae, Cucumovirus), and Tomato spotted wilt virus (Bunyaviridae, Tospovirus) have been detected in the samples. The obtained data allow to state a comparative diversity of plant viruses found in Antarctica.